Effects of vacuum packaging and temperature on minimally processed pre-cut mixed vegetables for pinakbet dish - Paglinawan, Arlyn Felix; Acevedo, Teresita P. (2001)
Minimally processed pre-cut pinakbet vegetables which included squash, okra, sitao, ampalaya and eggplant were packed in laminated nlon polyethylene and were stored 96 hours at 3 different temperatures: 30°C to 34°C, 1°C to 2°C and -16°C to -18°C. The physico-chemical and microbiological changes, as affected by vacuum packaging and storage temperature, were monitored throughout the storage. The vegetables stored at 30°C to 34°C (room temperature) showed abrupt decrease in pH after 72 hours. The titratable acidity (TA) and the moisture content of the vegetable increased during storage. Rate of enzymatic browning in eggplant and microbial population of th mixed vegetables in both packaging systems decreased after 72 hours. Quality deterioration was already visible after 96 hours of storage. The changes in pH after 96 hours were minimal for vegetable stored at 1°C to 2°C (refrigerated temperature) and at -16°C to -18°C(frozen temperature). Titratable acidity decreased upon storage while mixture remained unchanged. Rate of enzymatic browning in eggplant stored at frozen temperature was higher than the sample stored at 1°C to 2°C . Microbial population slightly increased after 96 hours. Results showed that vacuum packaging in combination with room temperature (30°C to 34°C) storage caused anaerobiosis in the sample that resulted to production of metabolites, affecting the physico-chemical and microbial characteristics of the sample. Low temperature slowed down the rate of respiration that caused minimal changes in the sample's physico-chemical and microbiologi
Thesis (BSFT)--University of the Philippines Diliman.
Keywords: Vegetables -- Packaging